2018
DOI: 10.1002/ece3.3950
|View full text |Cite
|
Sign up to set email alerts
|

Size‐assortative choice and mate availability influences hybridization between red wolves (Canis rufus) and coyotes (Canis latrans)

Abstract: Anthropogenic hybridization of historically isolated taxa has become a primary conservation challenge for many imperiled species. Indeed, hybridization between red wolves (Canis rufus) and coyotes (Canis latrans) poses a significant challenge to red wolf recovery. We considered seven hypotheses to assess factors influencing hybridization between red wolves and coyotes via pair‐bonding between the two species. Because long‐term monogamy and defense of all‐purpose territories are core characteristics of both spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 114 publications
2
31
0
Order By: Relevance
“…As a result, samples do not always reflect dingoes that do not encounter dogs. (3) There are some behavioural barriers that hinder hybridisation in canids (Hinton et al 2018). It is difficult for a feral domestic dog to integrate and compete with a large dingo population that has a stable pack structure (Corbett 2001b).…”
Section: Species Concepts and Delimitationmentioning
confidence: 99%
“…As a result, samples do not always reflect dingoes that do not encounter dogs. (3) There are some behavioural barriers that hinder hybridisation in canids (Hinton et al 2018). It is difficult for a feral domestic dog to integrate and compete with a large dingo population that has a stable pack structure (Corbett 2001b).…”
Section: Species Concepts and Delimitationmentioning
confidence: 99%
“…For red wolf ghost alleles to persist, a remnant Gulf Coast population would need to be relatively isolated from frequent interbreeding with coyotes [14]. Although red wolves that co-occur with coyotes in the NCEP exhibit assortative mating patterns [20], a geographic island would promote genetic isolation and the persistence of red wolf alleles. We report evidence that Galveston Island, Texas (TX) may represent one such location.…”
Section: Introductionmentioning
confidence: 99%
“…As such, coyote hybridization with remnant populations of eastern (C. lycaon) and/or gray wolves (C. lupus) has been documented along the northeastern expansion route (Kays et al, 2010;Rutledge, Garroway, Loveless, & Patterson, 2010;vonHoldt et al, 2011;vonHoldt, Kays, Pollinger, & Wayne, 2016), as well as with red wolves (C. rufus) in the southeastern expansion front (Nowak, 2002). In particular, red wolves are believed to be extirpated outside of the North Carolina recovery area, but hybridization between red wolves and coyotes is well documented within that area (Bohling et al, 2016;Hinton, Gittleman, Manen, & Chamberlain, 2018). Further, several previous studies have also shown that eastern coyote populations have interbred with domestic dogs (Adams, Leonard, & Waits, 2003;Wilson, Rutledge, Wheeldon, Patterson, & White, 2012;Wheeldon, Rutledge, Patterson, White, & Wilson, 2013;Monzõn, Kays, & Dykhuizen, 2014).…”
Section: Introductionmentioning
confidence: 99%